Irmandade de Nossa Senhora da Boa Morte de Cachoeira - BA: análise teológica do sincretismo em torno da Morte de Maria. - Amorim, Anderson Moura (2022)
The Brotherhood of Nossa Senhora da Boa Morte de Cachoeira, formed solely by black women, is characterized by devotion to Our Lady of Good Death and her Assumption into Heaven. Supported by the double religious belonging, to Catholicism and Candomblé, the sisters of Boa Morte, forged a religious syncretism capable of resisting and re-signifying values of both creeds, regarding the elements of death, in order to remain integrated in their multicultural context, marked by religious diversity. Our study consists of theologically analyzing the process of syncretism developed by the brotherhood of Boa Morte around Maria and Nanã Burokô/Burokê. For the elaboration of this study, bibliographic research was used as a methodology, enabling discussions on the historical and anthropological contextualization of the Irmandade da Boa Morte; understanding of death in Candomblé and the death of Mary in the Brotherhood's cosmovision and its syncretism between Nossa Senhora and Nanã; and, finally, a theological and pastoral analysis of the popular Christian faith in the face of the syncretism between Maria and Nanã, in the Brotherhood of Nossa Senhora da Boa Morte. Thus, the research results show that the Irmandade da Boa Morte celebrates the Catholic rituals of devotion to the Dormition of Mary, but, in fact, in an indirect way, it celebrates death according to its African ancestors, which imposes the observation that the syncretism carried out by the sisters, in the midst of the slave system, was a form of resistance and maintenance of cultural identity, as well as, from the theological point of view, this process reveals the resonances of the Spirit of God acting in hearts and religious traditions.